Rural Water Quality Monitoring and Exploring Low-Cost Treatment Technology with Water Hyacinth - Nayar, Renu; Patel, Rajani (Edelweiss Applied Science and Technology, 2021)
Ground water in general is clean and fresh. However, industrialization and urbanization together with intensified agricultural activity have led to increasing demands on one hand but to the potential for large scale release of contaminants on the other. Water pollution disturbs the normal uses of water for agriculture, public water supply, aquatic life, wild life and industry. An understanding of the various types of pollutants is of considerable importance to the efficient management of water resources. Inorganic pollutants discharged into natural waters consist of mineral acids, inorganic salts, metal compounds, complexes of metal and trace elements. The proposed investigation will evaluate the underground water quality of hand pump water and Tap water of Sirgitti in rural area and its surrounding industrial areas near 7 km from Bilaspur C.G. With this objective in mind, A new and low-cost technology for purification for water by water hyacinth (Eichhornia crassipes), is a feasible solution. Water samples were collected during the growth of water hyacinth. Water purification with low-cost treatment technology using water hyacinth. The common Water Hyacinth is vigorous growers known to double its population in only 12 to 15 days. In the Water Hyacinth area and the nearby area, water pH showed a decrease between the August and September sampling followed by an upward trend and stayed stable around 9.3 in the far water hyacinth area. Water transparency showed a slow increase in August and September, and then a gradual decline in October; generally, transparency was significantly lower in the water hyacinth area than in other areas. Water Hyacinth has been used in aquatic systems worldwide for waste water purification. It has tremendous capacity of absorbing nutrients and other substances from the water and hence brings the pollution load down. In the present study an attempt was made to find the potential of Water Hyacinth in the treatment of Tap and hand pump water near industrial area of Sirgitti. The parameters studied were pH, EC, DO, BOD, TDS, Salinity, Alkalinity and Turbidity. Six months of experimental investigation showed that water hyacinth reduced considerably all the physicochemical parameters and but increased the Dissolved Oxygen (DO) to a significant level therefore it is concluded that Water Hyacinth (Eichhornia crassipes) is highly efficient in purification of water in respect of physicochemical parameters.